2009
DOI: 10.1177/0961203309106643
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and outcome of digital gangrene in 2684 lupus patients

Abstract: The aim of the study is to assess the clinical characteristics, risk factors and outcome of patients with systemic lupus erythematosus (SLE) complicated with digital gangrene. In all, 2684 consecutive SLE inpatients admitted to Peking Union Medical College Hospital from December 1997 to August 2007 were studied. Demographic data, clinical features, laboratory findings as well as therapeutic regimens were systematically reviewed and a database was established. Cases with digital gangrene were identified and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 28 publications
1
66
0
Order By: Relevance
“…Treatment with corticosteroids decrease the hazard of amputation 9. Our patients had pulse methylprednisolone, cyclophosphamide, while the patients with APS also had anticoagulation with warfarin and aspirin.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Treatment with corticosteroids decrease the hazard of amputation 9. Our patients had pulse methylprednisolone, cyclophosphamide, while the patients with APS also had anticoagulation with warfarin and aspirin.…”
Section: Discussionmentioning
confidence: 89%
“…Liu et al 9 have also suggested other contributory factors such as disease duration, Raynaud's phenomenon, elevated CRP and dyslipidaemia. Plasma cholesterol and triglycerides were normal in both patients and only one patient had elevated CRP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In SLE patients, RP is frequently present and it is associated with pulmonary hypertension (10). Long disease duration, RP and elevated serum CRP were independent predictive factors for SLE to develop digital gangrene (11). In addition lupus nephritis and RP are significant risk factors for vascular thrombosis in SLE patients with positive antiphospholipid antibodies (12).…”
Section: Discussionmentioning
confidence: 99%
“…3 Several risk factors have been identified with digital ulcers in SLE, including duration of lupus, male gender, atherosclerosis, vasculitis, and AAS. 4 Liu et al 5 demonstrated that duration of disease, the presence of Raynaud's phenomenon, and high serum CRP levels were determinants of digital ulcer development in a cohort of 2,600 lupus patients. When we looked at the risk factors in our patient, she had a 10-year history of lupus, but her disease activity was under control with small oral doses of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%